IMPLEMENTASI PERENCANAAN PEMBELAJARAN MENYENANGKAN DENGAN PENDEKATAN BERBASIS ASET DI SD MUHAMMADIYAH PAKEM - Fitri Utami , Ari; Vera Santi , Eva; Fauziah , Muhardila (Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas PGRI Yogyakarta, 2022)
Teachers need to innovate learning to create a fun, dynamic learning atmosphere full of enthusiasm and challenges. The reality of learning plans is considered to be a burden on teachers, causing teachers to be less focused on creating fun and meaningful learning. Most teachers, including at SD Muhammadiyah Pakem, prefer the conventional learning model, namely lectures and assignments. The purpose of this study is to improve learning innovations carried out by classroom teachers. The results of this research are expected to be used by teachers as a reference to improve themselves in applying their learning methods into fun and meaningful learning, as well as optimizing the learning ability of students with an asset-based approach. This research method is classroom action research with precycles, cycles 1 and 2. Teachers try asset-based approach methods to design learning.accompanied by the headmaster as a lesson study partner (independent outside assessor). The result is that an asset-based approach can organize competition and resources, not focusing on shortcomings but thinking about successes and strengths to promote enjoyable learning.